ENHANCING STUDENTS’ VOCABULARY MASTERY THROUGH WORD SQUARE MODEL - Teguh Satria Amin; Yulia Sari Harahap (IKIP Siliwangi, 2022)
The research objective was determined how the students learning after using Word Square Model on vocabulary mastery of students. A quantitative research method with a quasi-experimental research design was used in this work. 44 students studying English education made up the study's sample. SPSS used as the data analysis method. The findings of the paired sample T test indicated that there was a difference between the average student learning outcomes for the experimental class's pre-test and post-test, with the output of pair 1 yielding a value of sig. (2 tailed) of 0.000 0.05. Based on the output pair 2's value of sig. (2 tailed) of 0.000 0.05, it was determined that there was a difference between the control class's pre- and post-test averages for student learning outcomes. Based on the output pair 2's value of sig. (2 tailed) of 0.000 0.05, it was determined that there was a difference between the control class's pre- and post-test averages for student learning outcomes. The sig value was calculated using the Independent T test findings. It indicated that there is a difference between employing the Word Square Model and lectures in terms of the average student learning outcomes (2 tailed) of 0.000 0.05. The Word Square Model is better for students’ vocabulary mastery, as may be inferred from the previous description. Keywords: Word Square, Vocabulary, Learning Outcomes